Fatigue in piezoelectric ceramic vibrational energy harvesting: A review. (15th July 2020) - Salazar, R.; Serrano, M.; Abdelkefi, A.
Highlights: This review presents methods on how crystal structures of piezoelectric materials are grown. This review consolidates existing energy harvesters with a focus on their modeling and fatigue life. Critical discussions and future recommendations are also provided. Abstract: Piezoelectric energy harvesters have been thoroughly investigated from a material or mechanical application viewpoint. The need to understand the potential lifespan of these materials in mechanical applications requires information from both fields. This review presents methods on how these crystal structures are grown, doping agents for these materials, the architecture of transduction patches, and the vibrational energy harvester architecture that these transduction patches are placed. The cyclic nature of the vibrational energy harvester induces cyclic fatigue in these patches depending on fabrication defects and transduction material. Cyclic strain induces fatigue life, but cyclic polarization also induces crack expansion in the transduction material. This review also consolidates existing energy harvesting systems to give a basis on the current modeling and performance to show the lack of knowledge on important lifespan degradation. Critical discussions and future recommendations are provided to direct focus onto fatigue investigations to push vibrational energy harvester development forward.